KEARIFAN LOKAL DAN PRAKTIK PENGELOLAAN HUTAN BAMBU PADA MASYARAKAT BALI - irma yeny; Dhani Yuniati; Husnul Khotimah (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2016)
The successful development of bamboo forests in Bali can be built through the culture of the forest society inter preted by the local wisdom. This research was aimed: 1) to review the role of local wisdom in developing bamboo forests in Kintamani district, Bangli; 2) to review the role of bamboo forests in the society in Kintamani district, Bangli. This research used qualitative approach through deepopen-interview technique with a list of questions, observations and documentations. The 10 respondents were chosen pur posively with a snowball method. The results showed that: 1) the existence of local wisdom in the form of palemahan, which inter pret the knowledge, values, rules and customar y laws in the people, had regulated the behavior and relationship between human and environment in Kintamani, then also contributed in developing bamboo forests; 2) the development of bamboo forests gave positive contributions on the social aspect (absorbed the labor force to 403 HOK/ha/year), the economic aspect (increased the farmer's income to Rp 14.292.795/member/year), and the hydrological aspect (added 3 new water springs)).